A Study Of "Low Cost Carriers" (LCC) And Full Service Carriers" (FSC) And The Implementation Of LCC In Iran - Sabbaghi, Ali (2009)
This research is a comparative study of the Low Cost Carrier (LCC) business model with the Full Service Carrier (FSC), and its implementation in Iran. It also set out the LCCS and FSCs strategies, services, air fleet and other aspects in operation in various countries.